2008
DOI: 10.4161/cbt.7.10.6539
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated inhibition of hTERT enhances chemosensitivity of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. However, there is no effective treatment for HCC. It has been shown that sustained activation of telomerase is essential for the growth and progression of HCC, suggesting that telomerase is a rational target for HCC therapy. Here, we investigated the effects of siRNA-mediated knockdown of hTERT, the catalytic and rate-limiting subunit of telomerase, on the sensitivity of HCC cells to cisplatin. While silencing of hTERT and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…Importantly, hepatocytes have been reported to tolerate telomere dysfunctions [37], reinforcing the tumorigenic impact of alcohol-, HBV-, and HCV-associated telomere damage in exposed individuals. Targeting telomerase is becoming a promising approach for the treatment of HCC [38-40] and our present results also support such an approach for treating the main causes of this disease. In contrast, our results suggest that targeting the cause-specific deregulation of telomere protective factors might be of interest in the prevention or the treatment of cirrhosis and HCC.…”
Section: Resultssupporting
confidence: 81%
“…Importantly, hepatocytes have been reported to tolerate telomere dysfunctions [37], reinforcing the tumorigenic impact of alcohol-, HBV-, and HCV-associated telomere damage in exposed individuals. Targeting telomerase is becoming a promising approach for the treatment of HCC [38-40] and our present results also support such an approach for treating the main causes of this disease. In contrast, our results suggest that targeting the cause-specific deregulation of telomere protective factors might be of interest in the prevention or the treatment of cirrhosis and HCC.…”
Section: Resultssupporting
confidence: 81%
“…Previous work supporting this research showed that downregulating hTERT using siRNA-mediated inhibition enhanced chemosensitivity in hepatocellular carcinoma cells in vitro (Guo et al, 2008). Furthermore, Kanzawa et al (2003) have demonstrated that knockdown of hTERT chemosensitized U87-MG cells toward TMZ.…”
Section: Discussionmentioning
confidence: 72%
“…2 and Table 2). The role of telomerase in tumorigenesis is well-established in many types of cancer, and high telomerase activity is linked to high tumor malignancy [18] and chemo-resistence [19], [20], [21]. The activation of telomerase is tightly regulated at the transcriptional level, with several studies indicating that TERT transcription is the rate-limiting step in telomerase expression [22].…”
Section: Discussionmentioning
confidence: 99%